2018
DOI: 10.1007/s00170-018-1866-4
|View full text |Cite
|
Sign up to set email alerts
|

Machinability and manufacturing cost in low-lead brass

Abstract: Today, commercially used brasses commonly contain 2 to 4 wt% lead. As the availability of low-lead and lead-free brass increases, there are environmental incentives for investigating the consequences of replacing the lead-containing brasses with lead-free equivalents. Generally, lead-free brass is expected to have a lower machinability than its lead-alloyed counterpart, implying a higher manufacturing cost. Thus, the aim of this study has been to quantify the added manufacturing cost by replacing a standard br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…In order to evaluate the industrial viability of replacing common lead-containing free-machining brass with CuZn21Si3P, a case study was performed at a Swedish SME. 18 The study consisted of a comparison of the manufacturing cost between CuZn39Pb3 and CuZn21Si3P at a Swedish SME producing indoor heating components. For the product in question, a part of a thermostatic radiator valve assembly, it was found that the material accounts for roughly 70% of the total manufacturing cost.…”
Section: Manufacturing Costmentioning
confidence: 99%
“…In order to evaluate the industrial viability of replacing common lead-containing free-machining brass with CuZn21Si3P, a case study was performed at a Swedish SME. 18 The study consisted of a comparison of the manufacturing cost between CuZn39Pb3 and CuZn21Si3P at a Swedish SME producing indoor heating components. For the product in question, a part of a thermostatic radiator valve assembly, it was found that the material accounts for roughly 70% of the total manufacturing cost.…”
Section: Manufacturing Costmentioning
confidence: 99%
“…From a purely manufacturing-economic standpoint, substitution of lead-containing brass with a lead-free alternative does not appear to be an economically viable option, but it is technically possible, satisfying the requirements of the enforced legislation [19]. As such, efforts were made into incorporating soft second phase particles (SPPs) in the microstructure of copper-base alloys to attain the positive effects of Pb.…”
Section: Introductionmentioning
confidence: 99%
“…Leaded brasses consist mostly of a two phase structure, namely the alpha and the beta phases, with the lead particles randomly distributed at the grain boundaries 4,5 . However, depending on the amount of zinc, brass as an alloy can exist with a single alpha-phase 6 .…”
Section: Introductionmentioning
confidence: 99%